An Assessment of the Effects of Iyengar Yoga Practice on the Health-Related Quality of Life of Patients with Chronic Respiratory Diseases: A Pilot Study - Maria-Jose Santana; Julia S-Parrilla; Judith Mirus; Martha A Loadman; Dale C Lien; David Feeny (Canadian Respiratory Journal)
OBJECTIVE: To assess the effects of an Iyengar yoga program (IYP) on patients with chronic respiratory diseases.